THE EFFECT OF COVID-19 PANDEMIC ANXIETY ON THE SMOOTH POSTPARTUM MOTHER'S BREAST MILK AT ROSELA HOSPITAL IN KARAWANG REGENCY, WEST JAVA PROVINCE, 2022 - Rosalia Rosalia; Ita Herawati (Lembaga Pengembangan Kinerja Dosen, 2022)
Background: Breast milk is a liquid generated by the mother's breast glands in the form of natural food or the most nutrient-rich and high-energy milk created during pregnancy, which is always accessible and free of contaminants (Intan & Fitria, 2020). Breast milk is a diet that includes all of the essential nutrients for the growth and development of infants (Liliek Fauziah, 2020). Postpartum refers to the period of time between the birth of the baby and the expulsion of the placenta from the uterus and the next six weeks or approximately 40 days, which are accompanied by the recovery of organs related to the womb, which undergo changes such as injuries and others related to childbirth. Research Aim: The research aims to examine the relationship between postpartum mother anxiety and the ease of nursing during the Covid-19 epidemic. Research Design: The research employs the method of analytical observation with a cross-sectional design. The sample consists of 59 postpartum mothers who gave birth between January and April of 2022. The analysis of data uses Chi Square. Research Results: This study resulted in the distribution of the frequency of the influence of the Covid-19 pandemic anxiety on the smoothness of breastfeeding as many as 24 people (40.7%) while on smooth breastfeeding for postpartum mothers as many as 33 people (55.9%), who experienced Covid19 anxiety levels in postpartum mothers. the medium category was 19 people (32.2%), the level of anxiety of the Covid-19 pandemic in postpartum mothers was low as many as 16 people (10.2%) while breastfeeding was not smooth in postpartum mothers as many as 26 people (44, 1%) P value: 0.000 which is smaller than (0.05). Conclusion and recommendation: With increasing levels of anxiety during the COVID-19 pandemic, the ability of postpartum mothers to breastfeed will be hindered. From this finding, the researcher makes a recommendation or input to postpartum women, namely to regulate their emotions so that they do not have worry over anything, particularly the covid-19 epidemic. In order to make the breast milk that will be given to the baby smooth.